Effects of dietary apple polyphenol supplementation on carcass traits, meat quality, muscle amino acid and fatty acid composition in finishing pigs. Issue 11 (29th October 2019) - Xu, Xiaojiao; Chen, Xiaoling; Chen, Daiwen; Yu, Bing; Yin, Jingdong; Huang, Zhiqing
Abstract : Dietary APP supplementation improves the carcass traits, meat color, meat flavor, and meat nutritional value in finishing pigs. Abstract : As health awareness is increasing, consumers have changed their focus with a desire to purchase safer, healthier, and higher quality and nutritional value meat. The aim of this study was to investigate whether dietary apple polyphenol (APP) supplementation in finishing pigs could provide pork with high quality and nutritional value. In the present study, 36 castrated Duroc × Landrace × Yorkshire pigs with an average body weight of 71.25 ± 2.40 kg were randomly divided into three treatments and fed with a basal diet supplemented with 0, 400, or 800 mg kg −1 APPs for 7 weeks. The results showed that dietary 800 mg kg −1 APP supplementation not only decreased backfat thickness and abdominal adipose tissue index but also decreased L* (lightness) and b* (yellowness) in the longissimus dorsi (LD) muscle. The LD muscle crude protein content, the proportions of essential amino acids, flavor amino acids, and total amino acids, as well as the amino acid transporter ( SLC7A1, SLC7A2, SLC7A7, SLC1A2 ) mRNA levels were increased by 800 mg kg −1 APPs. The proportions of docosahexaenoic acid and n-3 polyunsaturated fatty acid (PUFA) and the ratio of PUFA to saturated fatty acid in LD muscle were increased by 400 mg kg −1 APPs. Meanwhile, dietary 400 mg kg −1 and 800 mg kg −1 APP supplementation decreased the contents of blood urea nitrogen and total cholesterol, as well as increased the content of inosinic acid in LD muscle. In conclusion, these results suggested that dietary 800 mg kg −1 APP supplementation improved the carcass traits, meat color, and meat flavor in finishing pigs. These results also suggested that dietary 400 mg kg −1 and 800 mg kg −1 APP supplementation improved the meat nutritional value in finishing pigs. The present study provides effective evidence for the application of APP supplementation for healthy high-quality and nutritional value pork production.